Frequency of Cholestasis Among the Patients Suffering from Hepatitis E Virus - Muhammad Shahid, Adnan Ali, Hamid Mahmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Acute viral hepatitis (AVH) is a major health concern in developing nations in regard to morbidity and mortality. Cholestasis in the form of bile thrombi in canaliculi is common in acute hepatitis but rare in chronic hepatitis This study was designed to find the influence of cholestasis among the patients suffering from hepatitis E virus. The aim of this study was to determine the frequency of cholestasis among the patients suffering from viral hepatitis E. Methods: The design of this study was Descriptive Cross-Sectional Study design, and the duration of this study was from 30 January 2022 to 20 September 2022 at Department of Gastroenterology Sheikh Zayed Hospital Lahore. A total of 189 patients were enrolled were observed to determine the frequency of cholestasis among the patients suffering from viral hepatitis E. Consecutive non-probability sampling technique was ___ used to collect data from the patients. All the collected data were entered and analyzed into SPSS version 24. Data were stratified for age, gender and history of diabetes. Post stratification Chi-square test were applied taking p value of <0. 05 as statistically significant. Results: Age wise distribution among 189 patients were analyzed as n= 15-20 Years 11(5. 8%) 21-30 Years 13(6. 9%) 31-40 Years 45(23. 8%)41-50 Years 86(45. 5%) 51-60 Years16(8. 5%) 61-70 Years18(9. 5%). Mean age was 47. 95 years+ 14. 176 SD. Gender wise distribution among 189 patients were analyzed as n= Male was110(58. 2%) Female was 79(41. 8%). Duration of Disease among 189 patients were analyzed as n= Less than 3 months was 103(54. 5%) and more than 3 months was 86(45. 5%). History of diabetes among 189 patients were analyzed as n= Yes was found 94(49. 7%) and No was found 95(50. 3%). Distribution of cholestasis among 189 patients were analyzed as n= Yes was found 90 (47. 6%) and No was found 99(52. 4%). Conclusion: Based on our findings, the prevalence of cholestasis was 49. 7% is in the range of that found in general population. However, this is an evolving area with ongoing research and further assessments in prospective large studies are warranted. It is not possible to differentiate viral hepatitis based on clinical features, biochemical parameters, and severity of illness. Serological markers are essential for correct etiological diagnosis. However, cholestasis is found to be significantly associated with hepatitis-E infection. Keywords: cholestasis, viral hepatitis E, infection, ELISA